“El derecho a la protesta nos corresponde” Batallas discursivas y representaciones en el conflicto del subterráneo de Buenos Aires (2009-2010) - José Benclowicz; Matías Artese (Nuevo mundo - Mundos Nuevos, 2014)
Between 2009 and 2010 there was an important process of struggles starring by Buenos Aires metro workers, in demand of independent union recognition. The workers, led by different activists linked to the left-classism tradition, confronted successfully the service concessionaire, the union that monopolized the representation of the sector, and the national government, which supported that union. In this paper, we examine the discourses deployed by each of these actors on the other, trying to unravel the strategies of representation in play. It seeks to assess how these strategies - which are part of a discursive - ideological struggle for a hegemonic version of reality - favored or not the other actions developed by the different actors, contributing the success or failure of its purposes. The analysis indicates that the actions led by classist union tradition in the subway were accompanied by a clever discursive strategy that sought to prove the illegality of the actions of other actors.